The calcium: an early signal that initiates the formation of the nervous system during embryogenesis - Leclerc, Catherine; Moreau, Marc; Néant, Isabelle (Frontiers in Molecular Neuroscience, 2012)
The calcium (Ca2+) signalling pathways have crucial roles in development from fertilization through differentiation to organogenesis. In the nervous system, Ca2+ signals are important regulators for various neuronal functions, including formation and maturation of neuronal circuits and long-term memory. However, Ca2+ signals are also involved in the earliest steps of nervous system development including neural induction, differentiation of neural progenitors into neurons, and the neuro-glial switch. This review examines when and how Ca2+ signals are generated during each of these steps with examples taken from in vivo studies in vertebrate embryos and from in vitro assays using embryonic and neural stem cells. Also discussed is the highly specific nature of the Ca2+ signalling pathway and its interaction with the other signalling pathways involved in early neural development.